The presence of tomato leaf curl Kerala virus AC3 protein enhances viral DNA replication and modulates virus induced gene-silencing mechanism in tomato plants - Pasumarthy, Kalyan K (BioMed Central, 2011)
BACKGROUND: Geminiviruses encode few viral proteins. Most of the geminiviral proteins are multifunctional and influence various host cellular processes for the successful viral infection. Though few viral proteins like AC1 and AC2 are well characterized for their multiple functions, role of AC3 in the successful viral infection has not been investigated in detail. RESULTS: We performed phage display analysis with the purified recombinant AC3 protein with Maltose Binding Protein as fusion tag (MBP-AC3). Putative AC3 interacting peptides identified through phage display were observed to be homologous to peptides of proteins from various metabolisms. We grouped these putative AC3 interacting peptides according to the known metabolic function of the homologous peptide containing proteins. In order to check if AC3 influences any of these particular metabolic pathways, we designed vectors for assaying DNA replication and virus induced gene-silencing of host gene PCNA. Investigation with these vectors indicated that AC3 enhances viral replication in the host plant tomato. In the PCNA gene-silencing experiment, we observed that the presence of functional AC3 ORF strongly manifested the stunted phenotype associated with the virus induced gene-silencing of PCNA in tomato plants. CONCLUSIONS: Through the phage display analysis proteins from various metabolic pathways were identified as putative AC3 interacting proteins. By utilizing the vectors developed, we could analyze the role of AC3 in viral DNA replication and host gene-silencing. Our studies indicate that AC3 is also a multifunctional protein.